Competitiveness of African countries in agrifood products - Bouët, Antoine; Goundan, Anatole; Zaki, Chahir (International Food Policy Research Institute, 2020)
In this chapter, we will provide more detailed statistics concerning the (un)competitiveness of African economies in these three value chains. We first study African trade patterns (trade flows and prices) in the cereals, sugar, and vegetable oils value chains using statistics for both the continent and by country, by stage of processing, and by the destination of exports and source of imports. Then we present agricultural and trade policies adopted by rich, emerging, and African countries in these three value chains. We do not make any study here of causality between these policies and the trade performance of African agriculture. We just provide facts as they are revealed by data on trade flows and policies in order to analyze to the competitiveness of these value chains.